Overview on Green Concrete Comprised of Farming Waste Residues (International Journal of Innovative Research in Computer Science & Technology, 2021)
The rising global market for construction  has resulted in an increase in the usage of concrete. On the  other hand, traditional concrete-making materials are not  totally ecologically friendly, driving research towards  greener concrete alternatives. Agricultural wastes including  those from biodiesel production, coconut, sorghum, and the  paddy sector have been extensively studied in the past, and  the results demonstrate that such materials would be used in  construction. Repurposing agricultural by - products  materials in the construction might reduce dependence on  traditional cement resources while also lowering impact on  the environment, waste management, and sewage disposal. This article examines the usage of producing alternative  farming waste cementitious materials, including such  bamboo, cornmeal, wheat, olive, rattan, seashell, and other  substances, with the purpose of evaluating the positives and  cons of doing so. The employment of agricultural powder in  concrete throughout various forms, such as partial  anthracite or aggregate replacements, as well as fibre  reinforcements, is investigated in this study. Despite the use  of agricultural waste materials lowered specific concrete  properties, the publication's main conclusion is that  effective therapeutic processes and judicious selection of  materials should allow for the preparation of cement with  enhanced performance. The review and discussion in this  article should provide new knowledge and understanding of  a broader range of agricultural residues that could be used  to build greener, more responsible concrete.
Keywords: Environment; Green Concrete; Production; Sustainable; Waste Materials